YOUTH EDUCATION ISSUES IN THE PROCESS OF GLOBALISATION: YOUTH AS A STRATEGIC RESOURCE OF THE STATE - Vohidov Durbek (Western European Studies, 2024)
This article discusses the issues of youth education in our country in the process of globalization, the state policy implemented by youth as a strategic resource of the state.
Keywords: globalization; youth policy; resource; country